2023
DOI: 10.1590/1980-5373-mr-2022-0559
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Hot-rolled Ti-25Ta-xZr Alloys by Rietveld Method

Abstract: This paper aims to analyze the structure of the Ti-25Ta-xZr system alloys (x = 0, 10, 20, 30, and 40% wt.) after melting and hot-rolling by Rietveld's technique. The results confirm that zirconium acts as a β phase stabilizer (in which the Ti-25Ta-40Zr alloy is fully β in the as-cast condition), increases the lattice parameters of the phases, decreases the c/a ratio of the α phase, consequently, decreases the elastic modulus values (86 to 72GPa) and decreases the atomic packing factor (APF) of the alloys (60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Thus, it can be observed that the elastic modulus of the alloys studied in this work is closer to the human bone than the traditional alloys used [6,30,[43][44][45][46]. It is essential to highlight that a low modulus value is required to produce new metals for biomedical use to avoid the "stress shielding" effect.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, it can be observed that the elastic modulus of the alloys studied in this work is closer to the human bone than the traditional alloys used [6,30,[43][44][45][46]. It is essential to highlight that a low modulus value is required to produce new metals for biomedical use to avoid the "stress shielding" effect.…”
Section: Discussionmentioning
confidence: 89%